PENGARUH UMUR DAN JARAK KEHAMILAN TERHADAP KEJADIAN PERDARAHAN KARENA ATONIA UTERI - Purwanti, Sugi; Trisnawati, Yuli (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
Introduction: Hemorrhage is the first cause of maternal death in the time after delivery. Causes of bleeding either because Atoni uterine. Atoni uterine is condition that uncontraction uterine muscle after delivery of the placenta. Uterine contraction causes the blood vessels open at the implantation of the placenta is not closed. Atoni uterine is caused by reproductive organs do not function optimally. Healthy reproductive age around 20-35 years, so the risk of puerpuralis at the age of less than 20 years old and over 35 years of risk occurs atonic uterus. Spacing pregnancies too close also cause reproductive organ recovery is not maximized. The research objective was to determine the relationship of age and spacing of pregnancy on the incidence of hemorrhage due to uterine atony. Knowing the factors that most influence on the hemorrhage due to uterine atony. The research method was a quantitative survey with cross sectional approach, the population was that postpartum mothers in hospitals RSUD Margono Soekardjo 2014. Mothers with postpartum hemorrhage due to uterine atony 459 cases. The number of sample was a 156 respondents. Bivariate analysis used chi square and multivariate used regression logistic. Result: Â maternal age risk as much as 35.9%. Spacing pregnancies at risk as much as 33.3%. There is a relationship between maternal age and spacing pregnancies to hemorrhage due to atonic uterus (p value 0.045 and 0.007). Multivariate analysis showed that the influence of spacing pregnancies (p value 0.011 and B exp 2:47). Conclusion there is a relationship between gestational age and spacing pregnancies to hemorrhage due to atonic uterus. Respondents with spacing pregnancies risk pregnancies have a greater risk of 2:47 times for hemorrhage due to uterine atony. Keywords: maternal age, spacing of pregnancy, uterine atony